2022
DOI: 10.1002/smll.202107252
|View full text |Cite
|
Sign up to set email alerts
|

Iron Selenide‐Based Heterojunction Construction and Defect Engineering for Fast Potassium/Sodium‐Ion Storage

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/smll.202107252. Suitable anode materials with high capacityand long cycling stability, especially capability at high current densities, are urgently needed to advance the development of potassium ion batteries (PIBs) and sodium ion batteries (SIBs). Herein, a porous Ni-doped FeSe 2 /Fe 3 Se 4 heterojunction encapsulated in Se-doped carbon (NF 11 S/C) is designed through selenization of MOFs precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…The C 1s XPS spectra of FeSe 2 @CN-420, Fe 3 Se 4 @CN-500, and Fe 7 Se 8 @CN-700 contain two peaks at 284.1 and 285.5 eV, which are originated from the sp 2 CC and sp 3 C–C bonding, respectively (Figure b). , In addition, the high proportion of sp 2 CC bonding suggest the presence of graphitic carbon layers in these composites. The N 1s spectra of these composites can be divided into three peaks at ∼398.4, 400.2, and 401.6 eV, which correspond to the pyridinic, pyrrolic, and graphitic nitrogen bonding, respectively (Figure c), implying the existence of nitrogen-doped carbon layers in the Fe x Se y @CN composites. These results indicated that the phen ligands of [Fe­(phen) 2 ]­(Se 4 ) had been transformed to nitrogen-doped carbon materials in the pyrolysis process.…”
Section: Resultsmentioning
confidence: 99%
“…The C 1s XPS spectra of FeSe 2 @CN-420, Fe 3 Se 4 @CN-500, and Fe 7 Se 8 @CN-700 contain two peaks at 284.1 and 285.5 eV, which are originated from the sp 2 CC and sp 3 C–C bonding, respectively (Figure b). , In addition, the high proportion of sp 2 CC bonding suggest the presence of graphitic carbon layers in these composites. The N 1s spectra of these composites can be divided into three peaks at ∼398.4, 400.2, and 401.6 eV, which correspond to the pyridinic, pyrrolic, and graphitic nitrogen bonding, respectively (Figure c), implying the existence of nitrogen-doped carbon layers in the Fe x Se y @CN composites. These results indicated that the phen ligands of [Fe­(phen) 2 ]­(Se 4 ) had been transformed to nitrogen-doped carbon materials in the pyrolysis process.…”
Section: Resultsmentioning
confidence: 99%
“…; X ¼ S and Se) have been shown to possess more competitive theoretical capacity relative to carbonaceous materials on account of multi-electron redox reactions, a faster charge-transfer rate than conventional oxide counterparts associated with the easily broken M-S or M-Se bond, as well as a smaller volume change than a metal alloy. 8,[10][11][12][13][14][15] In particular, cobalt sulde (CoS 2 ), a prospective anode candidate supported by a four-electron reaction mechanism, has shown a considerable emergence of interest in all kinds of energy-storage elds, and which exhibits controllable structure features, rich redox sites, and exible valence adjustability. 16,17 But in the meanwhile, like other chalcogenides, CoS 2 reserving Na + via both intercalation and conversion mechanisms inevitably brings along some critical issues of inferior intrinsic conductivity and large voltage pulverization induced by detrimental volume expansion.…”
Section: Introductionmentioning
confidence: 99%
“…The synergistic effect between carbon framework and heterojunction contributed to a satisfactory capacity of 208.8 mAh g −1 after 2000 cycles at 8 A g −1 . [8] Pan et al introduced N-doped carbon and constructed a core-shell structure to improve the structural stability of iron selenides. The improved electron transfer facilitated by the carbon shell and inner void endowed by the core-shell structure maintained the structural integrity and good reversible reactions, guaranteeing excellent rate capability and long-term cycle performance.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Among them, transition metal selenides have gained massive interest due to their fascinating properties including favorable electrical conductivity and good electrochemical activity. [8,9] However, the realization of satisfactory performance is hindered by the poor cycling stability caused by the drastic volume changes under multiple reactions and sluggish reaction kinetic originating from the slow Na + diffusion in the electrodes. [10,11] To address these problems, three effective strategies are commonly utilized.…”
mentioning
confidence: 99%